Aspalathin improves glucose and lipid metabolism in 3T3‐L1 adipocytes exposed to palmitate. Issue 11 (15th September 2015) - Mazibuko, Sithandiwe E.; Joubert, Elizabeth; Johnson, Rabia; Louw, Johan; Opoku, Andrew R.; Muller, Christo J. F.
Abstract : Scope: Saturated‐free fatty acids, such as palmitate, are associated with insulin resistance. This study aimed to establish if an aspalathin‐enriched green rooibos extract (GRE) and, its major flavanoid, aspalathin (ASP) could contribute significantly to the amelioration of experimentally induced insulin resistance in 3T3‐L1 adipocytes. Methods and results: 3T3‐L1 adipocytes were cultured in DMEM containing 0.75 mM palmitate for 16 h to induce insulin resistance before treatment for 3 h with GRE (10 μg/mL) or ASP (10 μM). GRE and ASP reversed the palmitate‐induced insulin resistance. At a protein level GRE and ASP suppressed nuclear factor kappa beta (NF‐κB), insulin receptor substrate one (serine 307) (IRS1 (Ser 307 )) and AMP‐activated protein kinase phosphorylation and increased serine/threonine kinase AKT (AKT) activation, while only GRE increased glucose transporter four (Glut4) protein expression. Peroxisome proliferator‐activated receptor alpha and gamma (PPARα and γ), and carnitine palmitoyltransferase one (CPT1) expression were increased by ASP alone. Conclusion: Together these effects offer a plausible explanation for the ameliorative effect of GRE and ASP on insulin‐resistance, an underlying cause for obesity and type 2 diabetes.